Wybrane metody wielowymiarowej analizy statystycznej wspomagające segmentację międzyrynkową opartą na koncepcji celów i środków - Sobczak, Elżbieta (Selected methods of multidimensional statistical analysis facilitating intermarket segmentation based on means-end-chains concept, 2006)
The objective of the study is to assess the possibility of applying selected methods of multidimensional statistical analysis (MSA) for international market segmentation based on binary data, which identify consumer means-end-chains. The analysis was limited to methods of co-occurrence applied in marketing research.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 137-147